PRICE BEHAVIOR AND FORECASTING PRODUCER PRICES OF SHALLOTS IN THE SPECIAL REGION OF YOGYAKARTA - Al Rosyid, Ali Hasyim; Pratiwi, Liana Fatma Leslie (Journal of Agricultural Socio-Economics (JASE), 2024)
Shallots represent a significant component of Indonesia's vegetable crop production. They are widely consumed across the country, leading to an annual increase in demand. However, shallot production tends to remain stable or even decline, resulting in supply and price instability. In the Special Region of Yogyakarta, shallots are a prominent horticultural commodity with substantial production. Producer prices for shallots in this region exhibit fluctuations, particularly at the producer level compared to wholesale or consumer prices. Forecasting producer-level shallot prices utilizes the ARIMA (Autoregressive Integrated Moving Average) method, chosen for its accuracy in short-term time series prediction. Data sourced from the Strategic Food Price Information Center (PIHPS) via the hargapangan.id platform includes consumer prices and spans from January 2019 to May 2024. The analysis reveals that producer prices in the Special Region of Yogyakarta are influenced by previous month price increases, with the optimal ARIMA model identified as ARIMA (1,0,0) with the equation D(Y) = 21885.24 + 0.569977AR(1), as determined by the study findings.Keywords: ARIMA, Forecasting, Producer Prices, Shallots